Impact and Sustainability of Antibiotic Stewardship on Antibiotic Prescribing in Visceral Surgery - Magdalena Monika Gruber; Alexandra Weber; Jette Jung; Jens Werner; Rika Draenert (MDPI AG, 2021)
Background: Antibiotic stewardship (AS) ward rounds are a core element in clinical care for surgical patients. Therefore, we aimed to analyze the impact of surgical AS ward rounds on antibiotic prescribing, and the sustainability of the effect after the AS interventions are no longer provided. Methods: On four wards of the department of visceral surgery, we conducted two independent retrospective prescribing analyses (P1, P2) over three months each. During the study periods, the level of AS intervention differed for two of the four wards (ward rounds/no ward rounds). Results: AS ward rounds were associated with a decrease in overall antibiotic consumption (91.1 days of therapy (DOT)/100 patient days (PD) (P1), 70.4 DOT/100PD (P2)), and improved de-escalation rates of antibiotic therapy (W1/2: 25.7% (P1), 40.0% (P2), p = 0.030; W3: 15.4 (P1), 24.2 (P2), p = 0.081). On the ward where AS measures were no longer provided, overall antibiotic usage remained stable (71.3 DOT/100PD (P1), 74.4 DOT/100PD (P2)), showing the sustainability of AS measures. However, the application of last-resort compounds increased from 6.4 DOT/100PD to 12.1 DOT/100PD (oxazolidinones) and from 10.8 DOT/100PD to 13.2 DOT/100PD (carbapenems). Conclusions: Antibiotic consumption can be reduced without negatively affecting patient outcomes. However, achieving lasting positive changes in antibiotic prescribing habits remains a challenge.